Oncological Patients’ Willingness to Share Data in an Underperforming Healthcare System: The Case of Poland - Maria LIBURA; Joanna FLICINSKA-TURKIEWICZ; Bartosz SEKIEWICZ; Jakub RUTKOWSKI; Magdalena WLADYSIUK (Communications of International Proceedings, 2021)
Collecting and analysing data is crucial for development in medical sciences, as well as for improvement of healthcare systems performance. Patients willingness to share data is paramount to data-informed innovation in care pathways. This is especially important in oncology, where patient produced data become increasingly important as advances in personalised medicine are made and many oncological conditions become chronic diseases. Yet, the current understanding of factors influencing patients’ attitudes towards data sharing and use remains limited. The evidence is particularly scarce for underperforming healthcare systems, such as the one in Poland, which could in principle benefit the most from data-informed reform. The present paper is an attempt to address this issue in the Polish context, by focusing on factors which correlate with patients’ willingness to share data. Following a literature review, a mixed-method study design was adopted: first, a workshop with key opinion leaders in Polish oncology was conducted, which served to refine the list of plausible factors most likely to influence health data-sharing decisions. On this basis, four variables were identified for further investigation: patients’ satisfaction with information, patients’ expectations of care quality, trust toward the healthcare system, concerns with data sharing. Second, an online survey was designed and distributed among adult Polish oncological patients and patients’ caregivers. All of the variables were statistically significantly correlated with the willingness to share data.
Keywords: Willingness to share data; data security concerns; trust in healthcare system; expectations of care quality.